A Comparison of Microsatellites in Phytopathogenic Aspergillus Species in Order to Develop Markers for the Assessment of Genetic Diversity among Its Isolates - Mahfooz, Sahil; Singh, Satyendra P.; Mishra, Nishtha; Mishra, Aradhana (Frontiers in Microbiology, 2017)
Microsatellites (SSRs) are ubiquitously present in fungal genomes but vary greatly across species in their abundance. In the present study, we analyzed the frequency of SSRs in the whole genome and transcripts of two phyto-pathogenic (A. niger and A. terreus) and compared them with two non-pathogenic (A. nidulance and A. oryzae) Aspergilli. Higher relative abundance and relative density of SSRs were observed in the whole genome and transcript sequences of the pathogenic Aspergillus when compared to the non-pathogenic. The relative abundance and density of SSRs were positively correlated with the G+C content of transcripts. Among the different classes of SSR, the percentage of tetra-nucleotide SSRs were maximum in A. niger (36.7%) and A. oryzae (35.9%) whereas A. nidulance and A. terreus preferred tri-nucleotide SSRs (38.2 and 42.1%) in whole genome sequences. In transcripts, tri-nucleotide SSRs were the most abundant whereas di-nucleotide SSRs were the least favoured. Among all classes of repeats, 27.8% motifs were found conserved within Aspergillus species. Similar relationship among the ascomyceties was obtained on the basis of motif conservation and conserved genes (rDNA). Primers were successfully designed for 692 motifs in A. niger and A. terreus of which 20 were selected for diversity analysis among 23 Indian isolates of Aspergillus. Among all the markers amplified, 10 markers (83.3%) were polymorphic, whereas remaining two markers (16.6%) were monomorphic. Eleven polymorphic markers obtained in this study clearly demonstrate the utility of newly developed SSR markers in establishing genetic relationships among different isolates of Aspergillus.